(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The article discusses the possibilities of increasing the effectiveness of advertising means in modern electronic trade. The demand for modern advertising means has increased in Georgia, and the increase in the effectiveness of their use will help the development of electronic commerce in Georgia. The purpose of the study is to determine the prospects for the development of e-commerce in Georgia in the post-covid period, to study the possibilities of modern advertising means in this field, and to determine the ways of their implementation. Methods of collecting, grouping, and analyzing materials about electronic commerce were used in the development of the paper. The method of data collection is mainly used in the electronic trade system of Georgia, on the basis of which the possibilities of using modern advertising means in this field were identified and recommendations for their implementation were developed. In order to increase the competitiveness of the food and nutrition products produced in Georgia, it is necessary to improve the connections between the separate links of their production, to synchronize the production processes. In order to increase the level of food self-sufficiency of Georgia, it is necessary to protect the production of import-substituting, domestic, agrarian products with non-tariff barriers, and to properly manage their production and logistics. Significant and rapid changes in the global supply chain of food and nutrition products provoked by the Covid-19 pandemic have become an opportunity to increase the level of food self-sufficiency of Georgia, which needs to be properly used.